Collective climate action: When do people turn into collective environmental agents?. (December 2021) - Fritsche, Immo; Masson, Torsten
Abstract: Effectively protecting the climate requires the action of groups. In the present review article, we aim to understand when individuals turn into collective climate actors. We first discuss pertinent models of group-based action and their relevance for explaining climate action. Then, we review recent research on how collective climate action is driven by ingroup identification, social norms, group-based emotions, and collective efficacy. Finally, we focus on when and why people feel a sense of collective agency aiming at inspiring a novel research agenda on collective climate action.